BUDIDAYA IKAN LELE DAN TANAMAN KANGKUNG MELALUI SISTEM BUDIDAYA AQUAPONIK DI DESA SIDORAHARJO KECAMATAN KEDAMEAN KABUPATEN GRESIK - Miftakhul Jannah; Ahmad Lucky; Rama Ria Lesmana; Muhammad Firmansyah; Nia Suci Indaryani; Hanny Cherylla Jean Ananta; Julita Mega Purwanti; Reza Ayu Wulandari; Maria Evanirmala Subayang; Yana Jihan Almira; Wahyu Susiloningsih (Universitas PGRI Adi Buana Surabaya, 2023)
Aquaponic cultivation is a technique that is very easy to implement in Sidoraharjo Village because it has narrow land. Aquaponics is an aquaculture activity that is integrated with hydroponic activities. developing two different commodities, fish and vegetables in a Maintenance system on narrow landAquaponic technology is a combination of aquaculture technology and hydroponic technology in one system to optimize the function of water and space as a rearing medium. The plants will receive organic Aquaponic technology is a combination of aquaculture technology and hydroponic technology in one system to optimize the function of water and space as a rearing medium. The plants will receive organic fertilizer automatically from the remaining feed and fish waste. The advantage of using aquaponic cultivation is that plant nutrients can be obtained from feces and leftover fish food that settles at the bottom of the pond, so that quality water is produced that meets standards for fish farming. The stability of dissolved oxygen in water will be obtained from a water recirculation system in the form of a shower that results in collisions with pool water. In addition, the production of plants cultivated with the aquaponic system will be better than conventional because of the availability of sufficient water and additional nutrients from fish feces and food scraps.